Optimalisasi Manajemen Data, Penilaian Kinerja dan Disiplin Digital Bagi ASN di Dinas Cipta Bintar Kota Bandung - Zulvi, Lutfiani; Arwi, Ahwani Egiza; Rahma, Najla Aulia; Azzahra, Devina; Ariesmansyah, Andre (Innovative: Journal Of Social Science Research, 2025)
Digitalization has become a crucial aspect of public administration reform in Indonesia, including efforts to enhance the performance of the Dinas Cipta Karya, Bina Konstruksi, and Tata Ruang (Cipta Bintar) in Bandung City. This article outlines the urgency of optimizing three main elements: data management, digital performance evaluation, and digital discipline as the pillars of technology-based governance in this agency. Through the implementation of an integrated information system, the Dinas Cipta Bintar can manage spatial planning and construction data more efficiently, objectively evaluate the performance of civil servants, and enforce discipline through transparent digital mechanisms. The article also highlights key terms such as digital transformation, administrative efficiency, and performance accountability, while discussing strategies for implementation, challenges, and recommendations to maximize the benefits of digitalization in the Dinas Cipta Bintar.